Model eliciting activities: another tool for the elementary teaching toolbox. (2nd April 2020) - Parks, Melissa
Abstract: Maximizing classroom time to include meaningful content-based learning with fun engaging activities that simultaneously challenge and encourage students is a hallmark of a successful school day. This article shares one instructional approach that does a model eliciting activity (MEA). A MEA is a real-world, problem-based scenario framed around a fictitious client who writes a letter in which the client poses a problem for students to address. Students use the engineering design process to brainstorm, create, and test models, then compose written and oral responses to the client citing evidence to justify their solution. The content of the client letter is created by the classroom teacher and based on the Next Generation Science Standards, the teacher wishes to address. The depth of the content addressed is at the teacher's discretion and may vary depending on sequence of lessons within the unit of study, developmental readiness of students, and standard(s) selected.